Engineered exosome-mediated delivery of functionally active miR-26a and its enhanced suppression effect in HepG2 cells [Erratum] - Liang G (Dove Medical Press, 2018)
Liang G, Kan S, Zhu Y, et al. Int J Nanomedicine. 2018;13: 585–599. On page 586, the 1st heading, right hand column should read “Materials and methods” instead of “Patients and methods”.Read the original article.